Evaluación de la regeneración natural de pinus oocarpa Schiede, bajo planes de manejo en Dipilto Viejo, Nueva Segovia - González Morazán, L.M.; Ramírez Palma, O.D.; Calero Gonzalez, C.A. Asesor; Gonzalez Rivas, B. Asesor (Ocotal (Nicaragua), 2000)
Sumarios (Es, En)
Ilus.; 10 ref.
Tesis (Ing Agr)
Keywords: PINUS OOCARPA; REGENERACION NATURAL; SUELO FORESTAL; SILVICULTURA; BOSQUES; NICARAGUA; DIPILTO; NUEVA SEGOVIA